POTRET KONSEP DIRI SISWA PELAKU BULLYING (STUDI KASUS DI UPTD PPA DINAS DPPKBP3A DAN KANIT PPA POLRES KUNINGAN) - Ifan Fauzi, Muhamad; Sugiarti, Rini; Erlangga, Erwin (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2023)
School bullies often display repeated aggressive behavior with the aim of dominating or hurting their peers. The motives behind their actions can vary, ranging from a desire to demonstrate power, seek attention, or even resolve unresolved personal issues. The aim of this research is to determine the causes of the formation of self-concept in students who are bullies, as well as identifying internal and external factors that influence the formation of this self-concept. The research method used is qualitative, with a case study type. The data collection method is through interviews, observation and documentation. The interviews used were in-depth interviews, while the observations were non-participant, then documentation in the form of data from the Kuningan Police and UPTD PPA DPPKBP3A Service. Data analysis uses data reduction, data presentation, drawing conclusions. Validity of data with transferability test, dependability test and confirmability test. The subjects used were 2 students, the first one was at the Head of the Kuningan Police PPA Unit, and the other was at the UPTD PPA DPPKBP3A Service. The results of this research are that Subject FZ has a negative self-portrait because what FZ is proud of is influencing other people easily, so it would be very dangerous if anything he said that made other people's emotions rise. Meanwhile, the portrait of SL's self-concept is also quite negative, with the description of SL's character who easily believes other people's words, and SL's emotions have always been less able to be conditioned, meaning that in solving problems SL is used to using action rather than discussing first